Cobalt Complexes Supported by Phosphinoquinoline Ligands for the Catalyzed Hydrosilylation of Carbonyl Compounds. Issue 32 (26th April 2022) - Schiltz, Pauline; Casaretto, Nicolas; Auffrant, Audrey; Gosmini, Corinne
Abstract: P, N phosphinoquinoline based ligands differing by the nature of the phosphorus substituent ( i Pr, Ph) were employed to synthesize a series of cobalt(II) complexes ([LCoBr2 ], [L2 CoBr](PF6 ) and [L'2 CoBr](PF6 ) ). The latter were obtained in high yield and characterized among others by X‐ray analysis and elemental analysis. Complex [L2 CoBr](PF6 ) showed a very good catalytic activity for the hydrosilylation of various ketones. The catalysis proceeds at a low catalytic loading (1 mol %) with only 1 equivalent of Ph2 SiH2 in mild conditions and was efficient with aliphatic or aromatic ketones giving moderate to excellent yields of the corresponding silylated ether. Abstract : Phosphinoquinoline cobalt(II) complexes were used for the hydrosilylation of ketones. The diisopropylphosphino containing bisliganded complex was the most efficient allowing the transformation of variously substituted aliphatic or aromatic ketones at low catalyst loading and under mild conditions. The involvement of a Co−H complex as the active species was experimentally ascertained.